Respon Pertumbuhan Hipokotil Kurma (Phoenix dactylifera L.) cv. Barari Madu pada Beberapa Konsentrasi Zat Pengatur Tumbuh secara In Vitro - Novita Hidayatun Nufus; Aluh Nikmatullah; Muhammad Sarjan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
This study aims to determine the growth response of the hypocotyl date palm (Phoenix dactylifera L.) cv. Barari on several types and concentrations of Growth Regulators (PGR) in vitro. The research was carried out by planting 30-day-old hypocotyl dates on Murashige Skoog (MS) media by giving several concentrations of ZPT Naphthalene Acetic Acid (NAA) and Benzyl Amino Purine (BAP). The treatment given is; P0 (Media MS0, without the addition of PGR), P1 (Media MS+1 ppm NAA+1 ppm BAP), P2 (Media MS+2 ppm NAA+1 ppm BAP), and P3 (Media MS+3 ppm NAA+1 ppm BAP). Each treatment consisted of 20 explants with 3 replications. The parameters observed were: 1) the first time shoots/roots appeared; 2) percentage of explants forming roots; 3) percentage of explants forming shoots; and 4) the color of the explants in each treatment after 30 days. Observational data were analyzed descriptively. The results showed that the hypocotyl response of the Barari cultivar planted in treatments P1, P2, and P3 showed cell enlargement and elongation, in contrast to explants in treatment P0 which did not show any growth response. In treatments P1 and P2, cell elongation occurred until the 10th day followed by root formation on the 15th day after planting. The percentage of explants that formed roots at P1 and P2 were 21.67% and 16.67%, respectively. In the P3 treatment, the explants only experienced cell enlargement and elongation without the formation of shoots or roots. The color of the explants on P0 treatment was slightly brown green with black tips after 30 DAP. Explants planted at P1, P2, and P3 formed shoots or shoots+roots, the hypocotyl area remained green, shoots were greenish-white, and roots were white.